Cascading Crypthecodinium cohnii biorefinery: global warming potential and techno-economic assessment - Silva, Carla (2022)
ABSTRACT: Prior to the commissioning of a new industrial biorefinery it is deemed necessary to evaluate if the new project will be beneficial or detrimental to climate change, one of the main drivers for the sustainable development goals (SDG) of the United Nations. In particular, how SDG 7, Clean and Efficient Energy, SDG 3, Good Health and Well Being, SDG 9, Industry Innovation and Infrastructure, and SDG 12, Responsible Production and Consumption, would engage in a new biorefinery design, beneficial to climate change, i.e., fostering SDG 13, Climate Action. This study uses life cycle assessment methodology (LCA) to delve in detail into the Global Warming Impact category, project scenario GHG savings, using a conventional and a dynamic emission flux approach until 2060 (30-year lifetime). Water, heat and electricity circularity are in place by using a water recirculation process and a combined heat and power unit (CHP). A new historical approach to derive low and higher-end commodity prices (chemicals, electricity, heat, jet/maritime fuel, DHA, N-fertilizer) is used for the calculation of the economic indicators: Return of investment (ROI) and inflation-adjusted return (IAR), based upon the consumer price index (CPI). Main conclusions are: supercritical fluid extraction is the hotspot of energy consumption; C. cohnii bio-oil without DHA has higher sulfur concentration than crude oil based jet fuel requiring desulfurization, however the sulfur levels are compatible with maritime fuels; starting its operation in 2030, by 2100 an overall GHG savings of 73% (conventional LCA approach) or 85% (dynamic LCA approach) is projected; economic feasibility for oil productivity and content of 0.14 g/L/h and 27% (w/w) oil content, respectively (of which 31% is DHA), occurs for DHA-cost 100 times higher than reference fish oil based DHA; however future genetic engineering achieving 0.4 g/L/h and 70% (w/w) oil content (of which 31% is DHA), reduces the threshold to 20 times higher cost than reference fish oil based DHA; N-fertilizer, district heating and jet fuel may have similar values then their fossil counterparts.